Assistance of Student Literacy Activities of UIN K.H. Abdurrahman Wahid for Extraordinary Students at SLB Pri Pekalongan - Chonitsa, Ana; Amma Chorida Adila; Hendri Hermawan Adinugraha (Amala Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of the times and technology has had an impact on the personality and self-esteem of today's youth, such as the loss of social sense and concern for others in society. Therefore, there is literacy assistance for FTIK UIN K.H Abdurrahman Wahid Pekalongan students which aims to foster student awareness in the community, especially education in Special Schools with students with special needs. This community service method includes four stages, namely activity introduction, creativity education, rewarding, and activity documentation. The results of community service show that this activity produces social learning and increases student creativity in creating learning that is appropriate to the situations and conditions of students with special needs. Student creativity created in learning models includes singing learning models, image visualization, origami loving, telling stories, coloring pictures, storytelling, and playing guessing games. Thus, students not only gain new experiences but also ideas and creativity to increase sensitivity in the social environment of society